2018
DOI: 10.1371/journal.pone.0206595
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and Ebola survivorship in Liberia: Results from a longitudinal cohort study

Abstract: BackgroundSurvivors of the 2014–2016 West Africa Ebola epidemic have been reported to suffer high levels of stigmatization after return to their communities. We sought to characterize the stigma encountered by a cohort of Ebola survivors in Liberia over time.MethodsEbola-related stigma was assessed from June 2015 to August 2017 in 299 adolescent and adult Liberian Ebola Survivor Cohort participants at three month intervals using adapted HIV stigma scales scored from 0 to 10 according to the proportion of answe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 21 publications
6
69
1
3
Order By: Relevance
“…Our result identifies higher occurrence of internalised stigma when compared with the occurrence of total enacted stigma experienced by EVD survivors. Our result contrasts to findings reported in a Liberian longitudinal cohort study that employed a different stigma instrument [23] but is in line with a South African study that employed the same stigma tool to measure stigma among HIV/AIDS patients to that employed in our study [50]. The higher frequency of internalised stigma (negative self-perception) among EVD survivors in our study is a cause for concern and warrants further research attention as it can lead to low self-esteem, low self-efficacy, loss of hope for the future and can interfere with life goal achievement [51].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our result identifies higher occurrence of internalised stigma when compared with the occurrence of total enacted stigma experienced by EVD survivors. Our result contrasts to findings reported in a Liberian longitudinal cohort study that employed a different stigma instrument [23] but is in line with a South African study that employed the same stigma tool to measure stigma among HIV/AIDS patients to that employed in our study [50]. The higher frequency of internalised stigma (negative self-perception) among EVD survivors in our study is a cause for concern and warrants further research attention as it can lead to low self-esteem, low self-efficacy, loss of hope for the future and can interfere with life goal achievement [51].…”
Section: Discussioncontrasting
confidence: 99%
“…This is the first nationally representative study to determine the prevalence of stigma, its sociodemographic correlates and association with informal and nonintegrated forms of health care such as T&CM use among EVD survivors in Sierra Leone. One key finding from our study is that EVD survivors report high levels of internalised and enacted stigma since discharge from an Ebola treatment centre which is in line with findings from a longitudinal Liberian study that reported high levels of stigma at baseline but lower levels at subsequent follow-up visits [21,23]. Our finding also resonates with similar short term and smaller sample size cross-sectional studies in Sierra Leone [24,25,48], Liberia [20], Guinea [49], and DR Congo [19,40],which reported that EVD survivors experience several forms of internalised and enacted stigma.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Of the 3,385 individuals studied, 223 (6.6%) were found to have some degree of HL using audiometric evaluation and survey instruments. 19,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Only one of 21 articles used audiometry to objectively measure HL. This study, by Rowe et al, 19 recruited convalescent Ebola survivors and household contacts following the conclusion of the 1995 Ebola outbreak in Kikwit, DRC.…”
Section: Resultsmentioning
confidence: 99%
“…To address this knowledge gap, we revised the Berger HIV Stigma Scale (Berger-HSS) [35] to evaluate stigma associated with HCV infection. The Berger-HSS is a widely used measure of HIV stigma, which has been externally validated across HIV-infected patient populations within and outside of the US, [36][37][38][39][40][41][42][43][44][45][46][47] as well as adapted for use among non-HIV patient populations [48,49]. We hypothesized that the revised HCV Stigma Scale would have good validity and reliability among patients with HCV infection due to similarities with HIV in modes of transmission and risk factors.…”
Section: Introductionmentioning
confidence: 99%